(untitled) (Spectrum of Humanities and Social Sciences, 2025)
The journey of article publication is a rigorous academic undertaking that every academician and researcher aspires for and attempts. However, only a few of them can accomplish it to an ideal standard. The process consists of a series of interconnected steps from preparation to publication that begins with writing the initial draft as the primary step. Against this backdrop, this editorial illustrates effective academic strategies to help early-career authors meet the publication standards for an article. It reflects the editors’ cumulative empirical engagements across multiple scholarly roles of writing and publication, such as authorship, peer review, and editorial practices within diverse academic journals. Moreover, it sheds light on what truly happens behind the scenes of journal article publication. By blending our lived experiences and relevant, authentic literature, this editorial illustrates how early-career researchers can navigate the complexities of scholarly writing. It provides authorial guidelines to articulate local issues for national and international academic discourse through research undertakings, writing, and publication. It also discusses the relevant insightful ideas and practical steps to be acquired to transform the writing process into a final product (published article) within the publication standard. Ultimately, this editorial contributes to novice researchers in writing a publishable article in a peer-reviewed journal.